Study into the Fire and Explosion Characteristics of Polymer Powders Used in Engineering Production Technologies - Kuracina, Richard; Szabová, Zuzana; Buranská, Eva; Kosár, László; Rantuch, Peter; Blinová, Lenka; Měřínská, Dagmar; Gogola, Peter; Jurina, František (Polymers, 2023)
Polymers and their processing by engineering production technologies (injection, molding or additive manufacturing) are increasingly being used. Polymers used in engineering production technologies are constantly being developed and their properties are being improved. Granulometry, X-ray, FTIR and TGA were used to characterize polymer samples. Determination of the fire parameters of powder samples of polyamide (PA) 12, polypropylene, and ultra-high molecular weight (UHMW) polyethylene is the subject of the current article. An explosive atmosphere can be created by the powder form of these polymer materials, and introduction of preventive safeguards to ensure safety is required for their use. Although the fire parameters of these basic types of polymers are available in databases (e.g., GESTIS-DustEx), our results showed that one of the samples used (polypropylene) was not flammable and thus is safe for use in terms of explosiveness. Two samples were flammable and explosive. The lower explosive limit was 30 g·m−3 (PA12) and 60 g·m−3 (UHMW polyethylene). The maximum explosion pressure of the samples was 6.47 (UHMW polyethylene) and 6.76 bar (PA12). The explosion constant, Kst, of the samples was 116.6 bar·m·s−1 (PA12) and 97.1 bar·m·s−1 (UHMW polyethylene). Therefore, when using polymers in production technologies, it is necessary to know their fire parameters, and to design effective explosion prevention (e.g., ventilation, explosive-proof material, etc.) measures for flammable and explosive polymers.